Estudos flor?sticas e taxon?micos em Tibouchina Aubl. (Melastomataceae; Melastomeae) no Estado da Bahia, Brasil - Freitas, Juliana Gomes (2011)
This work represents a floristic and taxonomic study of the species of Tibouchina Aubl. (Melastomataceae) occurring in the state of Bahia, Brazil. It was done by fild trips trhought all vegetation types of Bahia and revision of the most representative herbaria of the state, and those which there were representative specimens from this region. Tibouchina is distribuited in the neotropics, especially in Brazil, where occur 150 of the 250 known species for the genus. In the present stude, 40 species were cataloged for Bahia, 14 have wide distribution in Brazil and only one of them is outside the country (T. stenocarpa (Schrank & Mart. ex DC.) Cogn.). Tibouchina crassiramis Cogn., T. elegans (Gardner) Cogn. and T. granulosa (Desr.) Cogn. correspond to the first record of occurrence to the northeast, and T. heteromalla (D. Don) Cogn. being quoted for the first time in Bahia. The other species (25) are endemic to the state, representing two new species described here (T. bracteolata J.G.Freitas, A.K.A.Santos & R.P.Oliveira and T. comosa J.G.Freitas, A.K.A.Santos & R.P.Oliveira), restricted to the Chapada Diamantina, and besides these, other seven taxa are also probably new (Tibouchina aff. heteromalla, T. aff. noblickii, T. aff. Paulo-alvinii, Tibouchina sp. 1, Tibouchina sp. 2, Tibouchina sp. 3 and Tibouchina sp. 4), but need to be better evaluated. The regions of Bahia with more representative of this genus are the Chapada Diamantina, where there are 24 species, nine of them endemic, and South and Southeast coasts of the state, where 12 species were recorded, four of them also endemic (T. bahiensis Wurdack, T. paulo-alvinii Vinha, T. salviifolia (Cham.) Cogn. and T. taperoensis Wurdack). Besides the macromorphological characters analyzed, those related to leaf indumentum, were very important in the taxonomy of the group, contributing to the separation of virtually all taxa occurring in Bahia. This work includes identification key for the species based on macromorphological characters and leaf indumentum, descriptions, illustrations, comments about morphology and geographical distribution of all species, and their place of occurrence in Bahia, as well as information about ecological and phenological aspects from all of them.